PENGARUH CAPITAL INTENSITY, INVENTORY INTENSITY, PROFITABILITAS DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK(STUDI KASUS PERUSAHAAN MANUFAKTUR SUB SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2022) - Evan Jasper; Dyah Mieta Setyawati (CV. ADIBA AISHA AMIRA, 2023)
Revenue from the Food and Beverage Sub Sector decreased by 16.3% (a condition of a declining economic cycle). Seeing this situation, business companies have the opportunity to take drastic tax measures to reduce the tax costs to be paid through tax planning and tax debt adjustments. The purpose of this study was to determine the effect of capital intensity, inventory intensity, profitability and leverage on tax aggressiveness in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2022 period. This research method is a quantitative approach and validation method. This research method is a quantitative approach and validation method. The result of this study is capital intensity, laverage has no influence on tax aggressiveness either partially or simultaneously. While Inventory Intensity, Profitability has an influence on Tax Aggressiveness